102k views
2 votes
Solve (−8x−12)+(9x+4)=

User Shatiz
by
5.4k points

2 Answers

2 votes
Simplifying
8x + -12 = 9x + -4 + x

Reorder the terms:
-12 + 8x = 9x + -4 + x

Reorder the terms:
-12 + 8x = -4 + 9x + x

Combine like terms: 9x + x = 10x
-12 + 8x = -4 + 10x

Solving
-12 + 8x = -4 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
-12 + 8x + -10x = -4 + 10x + -10x

Combine like terms: 8x + -10x = -2x
-12 + -2x = -4 + 10x + -10x

Combine like terms: 10x + -10x = 0
-12 + -2x = -4 + 0
-12 + -2x = -4

Add '12' to each side of the equation.
-12 + 12 + -2x = -4 + 12

Combine like terms: -12 + 12 = 0
0 + -2x = -4 + 12
-2x = -4 + 12

Combine like terms: -4 + 12 = 8
-2x = 8

Divide each side by '-2'.
x = -4

Simplifying
x = -4
User Krasnerocalypse
by
6.4k points
3 votes
We need to add like terms, meaning add the x's together and add the regular numbers together.

So if we add the x's together, -8x+9x = 1x.
Then when we add the numbers together, -12+4 = -8.

Combine our two sums and we get x-8 as the final answer.
User Rob Sawyer
by
6.5k points